2008
DOI: 10.1038/nature07276
|View full text |Cite
|
Sign up to set email alerts
|

Old-growth forests as global carbon sinks

Abstract: Old-growth forests remove carbon dioxide from the atmosphere at rates that vary with climate and nitrogen deposition. The sequestered carbon dioxide is stored in live woody tissues and slowly decomposing organic matter in litter and soil. Old-growth forests therefore serve as a global carbon dioxide sink, but they are not protected by international treaties, because it is generally thought that ageing forests cease to accumulate carbon. Here we report a search of literature and databases for forest carbon-flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

64
973
16
34

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,526 publications
(1,087 citation statements)
references
References 43 publications
64
973
16
34
Order By: Relevance
“…The results of this study show significantly greater effects of mature, broadleaved and state-owned forests on carbon storage than young and middle-aged, coniferous and community-owned forests. These results are consistent with the results from Luyssaert et al (2008). They also suggest an important management direction for Fujian Province in the design of future reforestation programs and further enhancement of vegetation carbon sequestration potentials.…”
Section: Discussionsupporting
confidence: 82%
“…The results of this study show significantly greater effects of mature, broadleaved and state-owned forests on carbon storage than young and middle-aged, coniferous and community-owned forests. These results are consistent with the results from Luyssaert et al (2008). They also suggest an important management direction for Fujian Province in the design of future reforestation programs and further enhancement of vegetation carbon sequestration potentials.…”
Section: Discussionsupporting
confidence: 82%
“…While young forests established on former agricultural lands, or burned and harvested forests for several years cannot compensate for the initial carbon loss nor contribute to CO 2 sequestration from the atmosphere, old forest stands retain their capacity to sequester CO 2 for long periods 31,32 . We show that the photosynthetic capacity and therefore the gross primary production of old growth forests are more resilient to climate variability than young forests.…”
mentioning
confidence: 99%
“…In addition, our study suggests that species-rich forest stands offer a larger potential for maintaining a stable photosynthetic capacity across time than species-poorer stands. Therefore, preserving our current forest (with old forests covering 15% of Earth's surface 32 ) and their species diversity may attenuate the annual fluctuations of global forest---atmosphere CO 2 exchange.…”
mentioning
confidence: 99%
“…Eventually, an unmanaged RF zone will reach a stage where net biomass accumulation becomes slow or even negative. What happens with SOC is not well understood, but it has recently been shown that old-growth upland forests generally are C sinks long after their net aboveground C storage has gone down (Luyssaert et al 2008).…”
Section: Managing Buffer Zones For C Storage and Ghg Balancementioning
confidence: 99%